Theoretical design of coumarin derivatives incorporating auxiliary acceptor with D-π-A-π-A configuration for dye-sensitized solar cells - Rattanawalee Rattanawan (2018)
© 2016 Elsevier B.V. All rights reserved. This study investigated the effects of incorporating benzothiadiazole (BTD) on the geometrical, photophysical, and electronic properties of coumarin-based dyes. New D-A-π-A and D-π-A-π-A systems arise from the presence of a BTD substituent, and we compare the properties these emergent systems to those of the pristine D-π-A system. The dyes were investigated on a theoretical basis using density functional theory (DFT) and time-dependent DFT methods. The new D-A-π -A and D-π-A-π-A structures have lower energy LUMOs and smaller energy gaps than the pristine dyes, resulting in significantly red-shifted absorption spectra. The substituted dyes may have application in improved light-harvesting ability. The delocalised ring systems present on BTD increase charge-transfer distances and provide a greater dipole moment, resulting in improvements to charge transfer properties over those of the unmodified dye. Additionally, D-π-A-π-A configuration shows efficiently electron injection from dye to TiO2. Compared with NKX-2510 reference dye, the absorption spectra of NCTBTA on TiO2surface exhibits a red shift up to 123 nm indicates remarkably stronger intramolecular charge transfer (ICT) and greatly improved electron injection efficiency. Our findings provide valuable information for the design of novel organic sensitizers for highly-efficient dye-sensitized solar cells.